AN ANALYSIS OF WOMAN’S STRUGGLE IN ‘FIVE FEET APART’ MOVIE BY JUSTIN BALDONI - Fasikh, Mukhlasul; Sumarwan, Sumarwan; Murtadho, Abdul Muhid (STIBA IEC JAKARTA, 2023)
This research is aimed to analyze the kind of woman’s struggle and Stella’s struggle to get in love in the ‘Five Feet Apart Movie’. This movie provides some struggles that are useful, they are struggle to get joy life, struggle in daily lives, and struggle to make end meet after life. The writers intend to know what kind of woman ‘s struggles found in “Five Feet Apart” Movie and how Stella’s struggles to get in love in “Five Feet Apart” Movie. The writers use qualitative methods to answer the problem. The writers apply the theory from Marsam (2000) about things that usually are fought in life. Therefore, the main purpose of this research is to analyze kind of woman’s struggle in “Five Feet Apart”, to analyze how Stella’s struggles to get in love in “Five Feet Apart” Movie. By studying kinds of woman’s struggling in this movie and how Stella’s struggle, it is implicated that the readers are encouraged to pursuing the struggling to be human being with touch to connect sadness, happiness, proud and all heart feeling